Pronunciation issues and EIL pedagogy in the periphery: A survey of Greek state school teachers’ beliefs’ - Sifakis, N.; A.-M. Sougari (TESOL Quarterly, 2005)
This article presents a survey of Greek EFL teachers' (N = 421) attitudes regarding their pronunciation beliefs and practices. It touches on two sets of questions. First, it refers to teachers' viewpoints regarding pronunciation-specific issues and the possible links between pronunciation teaching, English as an international language (EIL), and the sociocultural identity of nonnative speakers of English (NNSs). Second, it tries to establish the extent to which these teachers are aware of EIL-related matters, such as the need for mutual intelligibility in NNS-NNS communication. We conclude that teachers' viewpoints are predominantly norm bound. We further attempt to make sense of these viewpoints by referring to (a) the teachers' sense of being the custodians of the English language as regards English language learners and (b) the wider sociocultural linguistic background in Greece (which involves a history of diglossia and a recent experience of a massive inflow of immigrants). We go on to suggest ways to raise teachers' awareness of EIL-related concerns by suggesting that they use their immediate geopolitical and sociocultural surroundings.